Magnocellular-dorsal pathway and sub-lexical route in developmental dyslexia - Gori, Simone; Cecchini, Paolo; Bigoni, Anna; Molteni, Massimo; Facoetti, Andrea (Frontiers in Human Neuroscience, 2014)
Although developmental dyslexia (DD) is frequently associate to a phonological deficit, the underlying neurobiological cause remain undetermined. One prominent hypothesis suggests a specific deficit in magnocellular-dorsal (M-D) pathway. Here we investigated the visual M-D and parvocellular-ventral (P-V) pathway in dyslexic and in chronological age and IQ-matched normally reading children by measuring dynamic (frequency doubling illusion) and static stimuli sensibility, respectively. A specific deficit in M-D task was found. Importantly, the M-D deficit was selectively shown in poor phonological decoders. M-D deficit appears to be frequent because 75% of poor pseudo-word readers were at least 1 SD below the mean of the controls. Finally, a replication study by using a new group of poor phonological decoders and reading level controls suggests a possible role of M-D deficit in DD. These results showed that a M-D deficit might impair the sub-lexical mechanisms that are critical for reading development. The possible link between these findings and the oscillatory “temporal sampling” framework is discussed.